PERANCANGAN MULTI-CONSTRUCTIONAL POP-UP BOOK CERITA SAWUNGGALING SEBAGAI UPAYA PELESTARIAN LEGENDA ASLI SURABAYA UNTUK ANAK-ANAK - Prabandari, Titis Febri; Dewanto, Thomas Hanandry; Adrianto, Yosef Richo (Jurnal Art Nouveau, 2015)
Abstract: Surabaya is known as the city of heroes that rapidly growing into a metropolitan city. It is been called as the city of heroes for a good times does not make its local legend keeps alive and being told to the younger generations. On the contrary, they are gradually dulled and being thrown aside off the coming of more popular imported fairy tales. Effort needs to be made to create a more creative approach thus pick the younger generationâs interest to read local legends and fairy tales. Multi-constructional pop-up can be considered as one of the better approach. The design is done with observation, interview, and literature studies using keyword viewpoint literature review result namely kids, pop-up book, Sawunggaling legend, and Surabaya. By using qualitative method of analysis that is supported by indicators STP (Segmenting, Targeting and Positioning) and USP (Unique Selling Proposition)Â  obtained the word âjauntyâ that can be described into âhaving or expressing a lively, cheerful and self-confident mannerâ as the design concept. âSawunggaling â a Journey of an Epic Heroâ as the tittle with traditionally drew illustrations and multi-constructional pop-up designs as the point of interest.Â Keywords: Design, Illustration book, multi-constructional pop-ups, legends, Surabaya, Sawunggaling, jaunty